The Effect of Guided Inquiry Learning with Virtual Laboratory on Junior High School Students' Physics Learning Outcomes - Wilfridus Nggadung; Agus Wedi; Deka Dyah Utami (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2026)
Low physics achievement among junior high school students, particularly on the topics of work and energy, indicates the need for more effective instructional strategies. This study examined the effect of a guided inquiry approach assisted by PhET simulations on students’ learning outcomes in Work and Energy. A nonequivalent control group design was employed, involving 30 students in the experimental class and 30 students in the control class. The instrument consisted of 20 multiple-choice items designed to assess students’ understanding of fundamental concepts in Work and Energy. The results showed that the implementation of the PhET-assisted guided inquiry approach significantly improved students’ learning outcomes. This conclusion was supported by the results of an independent t-test and a high effect size. Nevertheless, the study was limited to a single topic and relied solely on quantitative data. Future research is therefore recommended to investigate other physics topics and to incorporate qualitative.